Future education for Modern world (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Throughout the globe, most of the teachers 'transmit factual knowledge to their students by adopting the transmission model, However, some countries have shifted their focus from transmission model to constructivist model. The main reason of adopting the transmission model is that it requires less disciplinary and pedagogical expertise from teachers as compared to constructivist model. Although transmission model increases the knowledge of the students but they are unable to apply if to new situation, communicating it in complex way, solve their problems and develop creativity. Students should learn the futuristic skill. Future education emphasise a paradigm shift to learn and teach 21st century skills.